Preparation method of self-cooling and self-cleaning nano coating for photovoltaic glass
By combining plant fibers and photocatalytic active nanomaterials, a self-cooling and self-cleaning nanocoating for photovoltaic glass was prepared, which solved the problem of dust and dirt accumulation in long-term outdoor use of photovoltaic glass coating and achieved high transmittance and self-cleaning effect and significantly reduce the temperature of the glass substrate.
Patent Information
- Application Number
- CN202411296423.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photovoltaic glass coating cannot effectively prevent the accumulation of dust and dirt during long-term outdoor use, resulting in reduced power generation efficiency of photovoltaic panels and poor self-cleaning effect.
Using a self-cooling and self-cleaning nanocoating, the fig leaf fig and rubber tree are crushed into pieces to form a plant fiber solution, and composite nanoparticles with titanium dioxide-antimony oxide, hollow silica-nickel-tin dioxide Combining composite nanoparticles and other materials, adding petroleum ether, titanium phosphate, potassium permanganate and other compounds to form a nanocoating coating liquid, using the light scattering characteristics of hollow particles and the redox effect of photocatalytic active materials to achieve high transmittance and self-transmittance Cleaning effect.
It achieves higher transmittance and self-cleaning effect, has excellent wear resistance and weather resistance, can decompose pollutants under ultraviolet irradiation, has waterproofness and antibacterial activity, and has significant cooling effect, which is suitable for industrial applications.
Smart Images

Figure CN119161758A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of self-cleaning coating preparation, and in particular relates to a method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass. Background Art
[0002] As energy resources become increasingly scarce, solar energy is considered a promising renewable energy source, and solar photovoltaic technology can convert light energy into electrical energy, so it has attracted widespread attention. In order to improve the conversion efficiency of photovoltaic panels and increase power generation, a coating is usually applied to photovoltaic glass, but there are still many problems. First, although the coatings currently on the market can increase the transmittance of sunlight on photovoltaic glass panels, they still cannot meet market demand. Second, during long-term outdoor use or in areas with less rain, the glass surface is prone to dust accumulation and bird droppings accumulation. These dirt particles will reflect / scatter / absorb the solar radiation incident on the glass material, resulting in insufficient sunlight incident on the surface of the photovoltaic panel, affecting the power generation efficiency.
[0003] A Chinese patent application with publication number CN 116285444 A discloses an indium-modified nano-silica permeability-enhancing liquid. The nano-silica particles are coated with a calcium fluoride layer, and the calcium fluoride layer is coated with an indium hydroxide layer. The coating has the advantages of high permeability, super hydrophilicity, and dustproofness. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass, so as to solve the problem that the existing self-cleaning coating has a poor effect.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass comprises the following steps:
[0007] S1, crushing the Ficus microcarpa and the rubber tree into pieces, adding water to the plant pieces for washing, and obtaining a plant solution containing plant fibers;
[0008] S2, adding titanium dioxide to deionized water and stirring, then adding antimony oxide and mixing, and placing in a heating furnace and heating at a high temperature of 520-600° C. for 3.5-5.5 hours to form titanium dioxide-antimony oxide composite nanoparticles;
[0009] S3, adding petroleum ether, titanium phosphate, potassium permanganate and sodium peroxide to the titanium dioxide-antimony oxide composite nanoparticles, mixing and stirring evenly to obtain a first solvent;
[0010] S4, adding hollow silica to deionized water and stirring, then adding nickel and tin dioxide, and placing in a heating furnace and heating at a high temperature of 800-1000° C. for 4-6 hours to form hollow silica-nickel-tin dioxide composite nanoparticles;
[0011] S5, adding acetone, sodium bicarbonate, and ethanol to the hollow silica-nickel-tin dioxide composite nanoparticles, mixing and stirring evenly to obtain a second solvent;
[0012] S6, mixing the first solvent and the second solvent and stirring them centrifugally, then adding isopropanol and deionized water, and continuing to stir to obtain a mixed solvent;
[0013] S7. After the mixed solvent and the plant solution are stirred and evenly mixed, a binder is added and the mixture is stirred evenly. After standing, a nano coating liquid is obtained.
[0014] Furthermore, in step S3, the mass ratio of titanium dioxide-antimony oxide composite nanoparticles, petroleum ether, titanium phosphate, potassium permanganate, and sodium peroxide is 5-10:7-15:10-15:8-16:12-18.
[0015] Furthermore, in step S5, the mass ratio of the hollow silica-nickel-tin dioxide composite nanoparticles, acetone, sodium bicarbonate, and ethanol is 6-10:10-15:12-16:30-45.
[0016] Furthermore, the binder is at least one of silica sol, polyurethane, acrylic acid, and fluorocarbon emulsion.
[0017] Furthermore, in step S1, the mass ratio of plant fragments to water is 1:1.2.
[0018] Furthermore, when the binder is added, the fluorocarbon emulsion and polyurethane are first added and stirred for a preset time, and then the acrylic acid and silica sol are added and stirred continuously.
[0019] Furthermore, the particle size of the hollow silica-nickel-tin dioxide composite nanoparticles is 60-80 nm, and the particle size of the titanium dioxide-antimony oxide composite nanoparticles is 70-90 nm.
[0020] Furthermore, the particle size of the silica sol is 4-6 nm.
[0021] Furthermore, after step S7, the self-cleaning nano coating is applied on the glass surface in a unidirectional manner from top to bottom.
[0022] The beneficial effects of the present invention are:
[0023] 1. In this application, hollow nano-silica is used as the main raw material, and the unique light scattering properties of hollow particles are utilized to achieve a higher transmittance. The obtained self-cleaning nano-coating liquid can be cured at room temperature and has excellent wear resistance and weather resistance. The present invention is relatively convenient to prepare, and a higher transmittance can be achieved without the need for multiple coating layers to be superimposed.
[0024] 2. Titanium dioxide in this application is a nanomaterial with photocatalytic activity, which can absorb light of a certain wavelength, generate free electrons and holes, and remove pollutants adsorbed on the surface of the film by redox decomposition, and kill surface microorganisms. Under ultraviolet irradiation, photocatalysts have a decomposition effect on organic matter, but have no effect on inorganic matter. In addition, the addition of fluorocarbon emulsion can make the self-cleaning nano coating of this application have extremely strong water resistance, and it can still work even after being damaged or contacted with oily substances.
[0025] 3. The air catalyst titanium phosphate used in this application can also achieve a self-cleaning effect in the absence of light, using only water and air. The mechanism of action of this material is to achieve the purpose of self-cleaning through the action of water and air in the absence of light.
[0026] 4. The nano material of the present application uses plant fiber to prepare a solution, which has a green and pollution-free effect. The Ficus microcarpa and the rubber tree used can absorb harmful substances in the air, such as dust, powder, etc. At the same time, the two can further adjust the temperature with the aforementioned compound material, which has a certain cooling effect. The plant cellulose and the first solvent and the second solvent form a nano coating liquid, which maintains the basic properties of cellulose and silk, and at the same time gives new functions, increasing antibacterial activity and ultraviolet absorption function.
[0027] 5. The nano coating of the present application has a significant cooling effect. When coated on the surface of a glass substrate, it can effectively reduce the temperature of the substrate. The cooling effect is combined with a self-cleaning effect, and is suitable for industrial applications.
[0028] 6. The present application uses silica sol, polyurethane, acrylic acid, and fluorocarbon emulsion as binders to ensure the firmness between titanium dioxide-antimony oxide composite nanoparticles and hollow silica-tin dioxide composite nanoparticles, thereby extending the service life of the film.
[0029] 7. The materials of the nano coating of the present application have the characteristics of high surface energy, high chemical activity and small size effect, which make them respond very sensitively to physical environments such as light, heat and electricity, thereby achieving a self-cleaning effect. At the same time, the preparation cycle of the present invention is short, and no long-term mixing and stirring and curing at a specific temperature are required, and a high transmittance can be achieved without the need for multiple coatings. In addition, the coating prepared by the present invention has extremely strong water resistance and can still function even after being damaged or contacted with oily substances.
[0030] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to make the purpose, technical solution and beneficial effects of the invention clearer, the present invention provides the following drawings for illustration:
[0032] Figure 1 is a flow chart of the preparation process of the present invention;
[0033] Figure 2 This is a schematic diagram of the effect of the self-cleaning nano coating of the present invention applied to the surface of a substrate. DETAILED DESCRIPTION
[0034] A method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass, such as Figure 1 As shown:
[0035] Example 1
[0036] S1, crush 20g of Ficus microcarpa and 20g of rubber tree into fragments with a particle size of 7cm, add the fragments into 50ml of pure water and wash until the plant fiber overflows, and filter out the fragments to obtain a plant solution containing the plant fiber;
[0037] S2, adding 3g of titanium dioxide to 3ml of deionized water and stirring, then adding 2g of antimony oxide and mixing, and placing in a heating furnace and heating at a high temperature of 550°C for 4 hours to form titanium dioxide-antimony oxide composite nanoparticles;
[0038] S3, adding petroleum ether, titanium phosphate, potassium permanganate and sodium peroxide to the titanium dioxide-antimony oxide composite nanoparticles, mixing and stirring evenly, wherein the mass ratio is 5:7:10:8:12, to obtain a first solvent;
[0039] S4, adding 3g of hollow silica to 3ml of deionized water and stirring, then adding 1g of nickel and 2g of tin dioxide, and placing in a heating furnace and heating at 800°C for 5 hours to form hollow silica-nickel-tin dioxide composite nanoparticles;
[0040] S5, adding acetone, sodium bicarbonate and ethanol to the hollow silica-nickel-tin dioxide composite nanoparticles, mixing and stirring evenly, wherein the mass ratio is 6:10:12:30, to obtain a second solvent;
[0041] S6, mixing the first solvent and the second solvent and centrifugally stirring for 30 minutes, then adding 20 ml of isopropanol and 25 ml of deionized water, and continuing to stir to obtain a mixed solvent;
[0042] S7, after the mixed solvent and the plant solution are stirred and mixed, 2g of fluorocarbon emulsion and 3g of polyurethane are added and stirred for 15min, and then 5g of acrylic acid and 4g of silica sol are added and stirred evenly, and after standing, a self-cleaning nano coating liquid is obtained;
[0043] S8. Remove the oil and debris on the surface of the glass substrate, rinse it with clean water, and wipe it dry with dust-free paper after cleaning; then use fiber cloth and scraper brush to absorb an appropriate amount of coating liquid and apply it to the glass surface from top to bottom in one direction;
[0044] S9. Place the coated glass sample in an oven and dry it at 110°C for 3-5 minutes.
[0045] In this application, hollow nano-silica is used as the main raw material, and the unique light scattering properties of hollow particles are utilized to achieve a higher transmittance. The obtained self-cleaning nano-coating liquid can be cured at room temperature and has excellent wear resistance and weather resistance. The present invention is relatively easy to prepare, and a higher transmittance can be achieved without the need for multiple coating layers to be superimposed.
[0046] Titanium dioxide in the present application is a nano material with photocatalytic activity, which can absorb light of a certain wavelength, generate free electrons and holes, and remove pollutants adsorbed on the film surface by redox decomposition, and kill surface microorganisms. Under ultraviolet irradiation, photocatalysts have a decomposition effect on organic matter and have no effect on inorganic matter. In addition, the addition of fluorocarbon emulsion preparation can make the self-cleaning nano coating of the present application have extremely strong water resistance, and can still work even after being damaged or contacted with oily substances.
[0047] In the present application, the air catalyst titanium phosphate can also achieve a self-cleaning effect in the absence of light, using only water and air. The mechanism of action of this material is to achieve the purpose of self-cleaning through the action of water and air in the absence of light.
[0048] The nanomaterial of the present application uses plant fibers to prepare solutions, which is green and pollution-free. The Ficus microcarpa and the rubber tree used can absorb harmful substances in the air, such as dust, powder, etc. At the same time, the two can further adjust the temperature with the aforementioned chemical substances, achieving a certain cooling effect.
[0049] The present application uses silica sol, polyurethane, acrylic acid, and fluorocarbon emulsion as binders to ensure the firmness between titanium dioxide-antimony oxide composite nanoparticles and hollow silicon dioxide-tin dioxide composite nanoparticles, thereby extending the service life of the film.
[0050] Example 2
[0051] The difference between Example 2 and Example 1 is that:
[0052] The mass ratio of titanium dioxide-antimony oxide composite nanoparticles, petroleum ether, titanium phosphate, potassium permanganate, and sodium peroxide is:
[0053] 10:8:10:15:15;
[0054] The mass ratio of hollow silica-nickel-tin dioxide composite nanoparticles, acetone, sodium bicarbonate and ethanol is 10:11:15.5:45.
[0055] Example 3
[0056] The difference between Example 3 and Example 1 is that:
[0057] The mass ratio of titanium dioxide-antimony oxide composite nanoparticles, petroleum ether, titanium phosphate, potassium permanganate, and sodium peroxide is: 5:15:14.5:8:12;
[0058] The mass ratio of hollow silica-nickel-tin dioxide composite nanoparticles, acetone, sodium bicarbonate and ethanol is 6:15:12:45.
[0059] In order to verify the superiority of the raw materials and preparation methods of the present invention, based on Example 1, Comparative Examples 1 to 4 are set up herein.
[0060] Comparative Example 1
[0061] S1, crush 20g of Ficus microcarpa and 20g of rubber tree into fragments with a particle size of 7cm, add the fragments into 50ml of pure water and wash until the plant fiber overflows, and filter out the fragments to obtain a plant solution containing the plant fiber;
[0062] S2, 3g titanium dioxide, 2g antimony oxide, 3g hollow silica, 1g nickel, 3g tin dioxide, 5g petroleum ether, 10g titanium phosphate, 8g potassium permanganate, 12g sodium peroxide, 10g acetone, 12g sodium bicarbonate, 30g ethanol, 2g fluorocarbon emulsion, 3g polyurethane, 5g acrylic acid, 4g silica sol were mixed and stirred to obtain a mixed solvent;
[0063] S3, stirring the mixed solvent and the plant solution to continue mixing, and letting them stand to obtain a coating solution;
[0064] S8. Remove the oil and debris on the surface of the glass substrate, rinse it with clean water, and wipe it dry with dust-free paper after cleaning; then use fiber cloth and scraper brush to absorb an appropriate amount of coating liquid and apply it to the glass surface from top to bottom in one direction.
[0065] Comparative Example 1 is used to demonstrate the superiority of the preparation method of the present invention.
[0066] Comparative Example 2
[0067] S1, adding 3g of hollow silica to 3ml of deionized water and stirring, then adding 3g of tin dioxide, and placing in a heating furnace and heating at 800°C for 5 hours to form hollow silica-tin dioxide composite nanoparticles;
[0068] S2, adding acetone, sodium bicarbonate and ethanol to the hollow silica-nickel-tin dioxide composite nanoparticles, mixing and stirring evenly, the mass ratio thereof is 6:10:12:30, to obtain a solvent;
[0069] S3, the solvents were mixed and centrifuged for 30 minutes, and then 20 ml of isopropanol and 25 ml of deionized water were added, and the mixed solvent was obtained by continued stirring, and the coating solution was obtained after standing;
[0070] S4. Remove the oil and debris on the surface of the glass substrate, rinse it with clean water, and wipe it dry with dust-free paper after cleaning; then use fiber cloth and scraper brush to absorb an appropriate amount of coating liquid and apply it to the glass surface from top to bottom in one direction;
[0071] S5. Place the coated glass sample in an oven and dry it at 110°C for 3-5 minutes.
[0072] Compared with Example 1, Comparative Example 2 lacks the plant solution and the first solvent, which is used to prove the superiority of the material of the present invention.
[0073] Comparative Example 3
[0074] S1, crush 20g of Ficus microcarpa and 20g of rubber tree into fragments with a particle size of 7cm, add the fragments into 50ml of pure water and wash until the plant fiber overflows, and filter out the fragments to obtain a plant solution containing the plant fiber;
[0075] S2, adding 3g of titanium dioxide to 3ml of deionized water and stirring, then adding 2g of antimony oxide and mixing, and placing in a heating furnace and heating at a high temperature of 550°C for 4 hours to form titanium dioxide-antimony oxide composite nanoparticles;
[0076] S3, the solvents were mixed and centrifuged for 30 minutes, and then 20 ml of isopropanol and 25 ml of deionized water were added, and the mixture was stirred continuously to obtain a mixed solvent;
[0077] S4, allowing the mixed solvent to stand to obtain a coating solution;
[0078] S5. Remove the oil and debris on the surface of the glass substrate, rinse it with clean water, and wipe it dry with dust-free paper after cleaning; then use fiber cloth and scraper brush to absorb an appropriate amount of coating liquid and apply it on the glass surface from top to bottom in one direction;
[0079] S6. Place the coated glass sample in an oven and dry it at 110°C for 3-5 minutes.
[0080] Compared with Example 1, Comparative Example 3 lacks the plant solution and the second solvent, which is used to prove the superiority of the material of the present invention.
[0081] Comparative Example 4
[0082] S1, crush 20g of Ficus microcarpa and 20g of rubber tree into fragments with a particle size of 7cm, add the fragments into 50ml of pure water and wash until the plant fiber overflows, and filter out the fragments to obtain a plant solution containing the plant fiber;
[0083] S2, adding 1.5 g of titanium dioxide to 3 ml of deionized water and stirring, then adding 2 g of antimony oxide and mixing, and placing in a heating furnace and heating at a high temperature of 550° C. for 4 hours to form titanium dioxide-antimony oxide composite nanoparticles;
[0084] S3, adding petroleum ether, titanium phosphate, potassium permanganate and sodium peroxide to the titanium dioxide-antimony oxide composite nanoparticles, mixing and stirring evenly, the mass ratio thereof is 3:20:5:20:20, to obtain a first solvent;
[0085] S4, adding 3g of hollow silica to 3ml of deionized water and stirring, then adding 0.5g of nickel and 6g of tin dioxide, and placing in a heating furnace and heating at 800°C for 5 hours to form hollow silica-tin dioxide composite nanoparticles;
[0086] S5, adding acetone, sodium bicarbonate and ethanol to the hollow silica-nickel-tin dioxide composite nanoparticles and mixing them evenly in a mass ratio of 15:5:8:60 to obtain a second solvent;
[0087] S6, mixing the first solvent and the second solvent and centrifugally stirring for 30 minutes, then adding 20 ml of isopropanol and 25 ml of deionized water, and continuing to stir to obtain a mixed solvent;
[0088] S7, after the mixed solvent and the plant solution are stirred and mixed, 1g of fluorocarbon emulsion and 1g of polyurethane are added and stirred for 15 minutes, and then 1g of acrylic acid and 1g of silica sol are added and stirred evenly, and the coating solution is obtained after standing;
[0089] S8. Remove the oil and debris on the surface of the glass substrate, rinse it with clean water, and wipe it dry with dust-free paper after cleaning; then use fiber cloth and scraper brush to absorb an appropriate amount of coating liquid and apply it to the glass surface from top to bottom in one direction;
[0090] S9. Place the coated glass sample in an oven and dry it at 110°C for 3-5 minutes.
[0091] Compared with Example 1, the ratio of the first solvent, the second solvent and the binder in Comparative Example 4 is not within the scope of protection of the present application, and is used to demonstrate the superiority of the material ratio and bonding performance of the present invention.
[0092] The self-cleaning nano coatings of Examples 1-3 and the glass coatings prepared in Comparative Examples 1-4 were placed in the same open-air environment, with conditions such as light, ultraviolet rays, and rainwater scouring, and the performance was compared after 7 days. The temperature test method is: all substrates are placed under the same sunlight temperature, and after 2 hours, the side of the glass substrate that is not coated with the nano coating is tested, and then the glass is coated on the surface of the glass substrate, and after 2 hours, the glass is tested again, and the performance results can be measured, as shown in Table 1:
[0093] Table 1
[0094]
[0095] As can be seen from the above table, the self-cleaning nano coatings of Examples 1 to 3 prepared by the preparation method, raw materials and proportions of the present invention, after ultraviolet irradiation and rain washing, the performance of the materials remains good, there is no obvious dust and particles on the surface, and the surface is still smooth, no blistering or cracking occurs, the cooling effect is significant, and the temperature on the back of the substrate is effectively reduced. However, Comparative Example 1 does not adopt the preparation method of the present invention, Comparative Example 2 and Comparative Example 3 lack the raw materials of the present invention, and the proportion of Comparative Example 4 is not within the scope of the present invention. The coating effects obtained are not as good as the self-cleaning nano coating of the present invention. After being placed in a harsh environment, there is obvious dust on the surface, and some of them have more obvious granular substances. The glossiness is also significantly affected after testing, and the surface also has blistering and cracking. In addition, the cooling effect of the substrate is not significantly improved under sunlight, and the temperature is still high.
[0096] In summary, only by combining the preparation method, raw materials and mixing ratio of the present invention to obtain the self-cleaning nano coating can its performance in all aspects be optimized. The lack of any one of the steps will affect the performance of the product.
[0097] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass, Features: The following steps are included: S1, crushing the Ficus microcarpa and the rubber tree into pieces, adding water to the plant pieces for washing, and obtaining a plant solution containing plant fibers; S2, adding titanium dioxide to deionized water and stirring, then adding antimony oxide and mixing, and placing in a heating furnace and heating at a high temperature of 520-600° C. for 3.5-5.5 hours to form titanium dioxide-antimony oxide composite nanoparticles; S3, adding petroleum ether, titanium phosphate, potassium permanganate and sodium peroxide to the titanium dioxide-antimony oxide composite nanoparticles, mixing and stirring evenly to obtain a first solvent; S4, adding hollow silica to deionized water and stirring, then adding nickel and tin dioxide, and placing in a heating furnace and heating at a high temperature of 800-1000° C. for 4-6 hours to form hollow silica-nickel-tin dioxide composite nanoparticles; S5, adding acetone, sodium bicarbonate, and ethanol to the hollow silica-nickel-tin dioxide composite nanoparticles, mixing and stirring evenly to obtain a second solvent; S6, mixing the first solvent and the second solvent and stirring them centrifugally, then adding isopropanol and deionized water, and continuing to stir to obtain a mixed solvent; S7. After the mixed solvent and the plant solution are stirred and evenly mixed, a binder is added and the mixture is stirred evenly. After standing, a nano coating liquid is obtained.
2. A method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 1, Features: In step S3, the mass ratio of titanium dioxide-antimony oxide composite nanoparticles, petroleum ether, titanium phosphate, potassium permanganate, and sodium peroxide is 5-10:7-15:10-15:8-16:12-18.
3. The method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 1, Features: In the step S5, the mass ratio of the hollow silica-nickel-tin dioxide composite nanoparticles, acetone, sodium bicarbonate, and ethanol is 6-10: 10-15: 12-16: 30-45.
4. The method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 1, Features: The binder is at least one of silica sol, polyurethane, acrylic acid and fluorocarbon emulsion.
5. The method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 1, Features: In the step S1, the mass ratio of the plant fragments to water is 1:1.
2.
6. The method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 4, Features: When the binder is added, fluorocarbon emulsion and polyurethane are first added and stirred for a preset time, and then acrylic acid and silica sol are added and stirred continuously.
7. The method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 1, Features: The particle size of the hollow silicon dioxide-nickel-tin dioxide composite nanoparticles is 60-80 nm, and the particle size of the titanium dioxide-antimony oxide composite nanoparticles is 70-90 nm.
8. The method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 1, Features: The particle size of the silica sol is 4-6 nm.
9. The method for preparing a self-cooling and self-cleaning nano coating for photovoltaic glass according to claim 1, Features: After step S7, the self-cleaning nano coating is applied on the glass surface in a unidirectional manner from top to bottom.
Citation Information
Cited By
Self-assembled gradient multifunctional photovoltaic glass coating and preparation method thereof
CN121975436A
